First operation of the JUNGFRAU detector in 16-memory cell mode at European XFEL - Sikorski, Marcin; Ramilli, Marco; de Wijn, Raphael; Hinger, Viktoria; Mozzanica, Aldo; Schmitt, Bernd; Han, Huijong; Bean, Richard; Bielecki, Johan; Bortel, Gábor; Dietze, Thomas; Faigel, Gyula; et al. (Frontiers in Physics, 2023)
The JUNGFRAU detector is a well-established hybrid pixel detector developed at the Paul Scherrer Institute (PSI) designed for free-electron laser (FEL) applications (1). JUNGFRAU features a charge-integrating dynamic gain switching architecture (2, 3), with three different gain stages and 75 µm pixel pitch. It is widely used at the European X-ray Free-Electron Laser (EuXFEL), a facility which produces high brilliance X-ray pulses at MHz repetition rate in the form of bursts repeating at 10 Hz. In nominal configuration, the detector utilizes only a single memory cell and supports data acquisition up to 2 kHz. This constrains the operation of the detector to a 10 Hz frame rate when combined with the pulsed train structure of the EuXFEL. When configured in so-called burst mode, the JUNGFRAU detector can acquire a series of images into sixteen memory cells at a maximum rate of around 150 kHz. This acquisition scheme is better suited for the time structure of the X-rays as well as the pump laser pulses at the EuXFEL. To ensure confidence in the use of the burst mode at EuXFEL, a wide range of measurements have been performed to characterize the detector, especially to validate the detector calibration procedures. Special attention was given to the transitions between gain stages. The detector was operated in both dynamic gain switching and fixed gain modes. Based on the promising outcome of those studies, all memory cells were used during two experiments at EuXFEL. Here, we highlight current experimental capabilities of the burst mode.